2012
DOI: 10.1038/nbt.2464
|View full text |Cite
|
Sign up to set email alerts
|

Mass-encoded synthetic biomarkers for multiplexed urinary monitoring of disease

Abstract: Biomarkers are increasingly important in the clinical management of complex diseases, yet our ability to discover new biomarkers remains limited by our dependence on endogenous molecules. Here we describe the development of exogenously administered `synthetic biomarkers' composed of mass-encoded peptides conjugated to nanoparticles that leverage intrinsic features of human disease and physiology for noninvasive urinary monitoring. These protease-sensitive agents perform three functions in vivo: target sites of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
255
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(261 citation statements)
references
References 44 publications
(55 reference statements)
2
255
0
Order By: Relevance
“…We previously showed that synthetic biomarkers composed of long-circulating NWs accumulate in diseased tissue by diffusing across fenestrated vessels such as in liver fibrosis and cancer (8), or when the sites of disease are intravascular as in thrombosis, sense protease activity while in systemic circulation (9). These studies also showed that free peptides administered i.v.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…We previously showed that synthetic biomarkers composed of long-circulating NWs accumulate in diseased tissue by diffusing across fenestrated vessels such as in liver fibrosis and cancer (8), or when the sites of disease are intravascular as in thrombosis, sense protease activity while in systemic circulation (9). These studies also showed that free peptides administered i.v.…”
Section: Resultsmentioning
confidence: 98%
“…To develop synthetic biomarkers for thrombosis and cancer, we first sought to design NPs for sensing the activity of the proteases thrombin and matrix metalloproteinase 9 (MMP9). We functionalized poly(ethylene glycol)-coated iron oxide nanoworms (NWs)-a long-circulating NP formulation previously characterized by collaborators and our laboratory (19,20)-with fluorescein-labeled derivatives of thrombin-and MMP9-cleavable substrates [PLGLRSW and PLGVRGK, respectively (8)] at a surface valency of 20-30 peptides per NW to induce intermolecular quenching (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The extensive suite of proteases and protease recognition sites-any of which could be introduced into the sequence at one or more arbitrary positions-should provide a versatile toolbox for controlling IDP brush properties in a dynamic and specific manner. Analogous enzymatically addressable materials have been explored for a variety of applications such as payload delivery 42 , diagnostic monitoring 43 and ligand presentation [44][45][46] . Although much effort has been focused on understanding the biological function of endogenous IDPs, our study suggests that these proteins represent an untapped resource for biomaterial design.…”
Section: Discussionmentioning
confidence: 99%